Persistence of Hepatitis A Virus RNA in Water, on Non-porous Surfaces, and on Blueberries - Trudel-Ferland, Mathilde; Jubinville, Eric; Jean, Julie (Frontiers in Microbiology, 2021)
Enteric viruses, such as human norovirus and hepatitis A virus (HAV), are the leading cause of transmissible foodborne illness. Fresh produce such as berries are often contaminated by infected food handlers, soiled water or food contact surfaces. The gold-standard method for virus detection throughout the food chain is RT-qPCR, which detects portions of genomes including non-infectious viral particles and naked viral RNA. The aim of this study was to evaluate the persistence of heat-inactivated HAV in water, phosphate-buffered saline, on stainless steel and polyvinyl chloride and on blueberries at -80°C, -20°C, 4°C and room temperature. In water and phosphate-buffered saline, viral RNA could be detected for up to 90 days regardless of temperature when the initial load was 2.5 × 10^4 or 2.5 × 10^6 genome copies. It was detected on polyvinyl chloride and blueberries under most conditions. On stainless steel, the large initial load persisted for 90 days while the medium-level load was detected only up to 16 days at room temperature or 60 days at 4°C. The detection of non-infectious viral RNA can confound investigations of gastroenteritis outbreaks. Pretreatments that discriminate between naked RNA, non-infectious virions and infectious virions need to be included in the RT-qPCR method in order to reduce the risk of positive results associated to non-infectious viral particles.